Synthesis of α‐Amidoacrylates Containing a 3‐Ylideneoxindole Motif. Issue 13 (7th April 2021) - Song, Shuai; Li, Ya; Chen, De‐Yin; Wang, Xiao‐Ping; Liu, Yong‐Liang; Chen, Ling‐Yan
Abstract: Both the α‐amidoacrylate and 3‐ylideneooxindole frameworks are important in medicinal chemistry because of their associated biological activities. We report a novel approach to accessing α‐amidoacrylates containing a 3‐ylideneoxindole motif through a novel cascade process involving condensation between 3‐fluorooxindoles and α‐iminoacetates followed by elimination of HF. This protocol has a broad substrate scope: N ‐alkyl‐, N ‐aryl‐, N ‐allyl‐, N ‐propargyl 3‐fluorooxindoles and 3‐fluorooxindoles with different substituents on the aromatic rings were all suitable for this reaction. A plausible reaction pathway is also presented. Abstract : α‐Amidoacrylates containing a 3‐ylideneoxindole motif has been synthesized starting from 3‐fluorooxindoles and α‐iminoacetates through an addition/elimination cascade process. α‐[ N ‐( tert ‐butanesulfinyl)imino]acetate and α‐(phenylimino)acetate can participate in the reaction and N ‐methyl, N ‐ethyl, N ‐benzyl, N ‐phenyl and N ‐propargyl 3‐fluorooxindoles are all suitable substrates for the reaction and gave the corresponding products in good to excellent yields.. A single fluorine substitution has a beneficial effect on promoting the reaction. A plausible mechanism has been presented.